Mortality associated with seasonal changes in ambient temperature and humidity in Zenica-Doboj Canton - Suad Sivić (Medicinski glasnik, 2021)
Aim: To determine the relationship between seasonal changes in ambient temperature, humidity and general and specific mortality rates in the area of Zenica-Doboj Canton. Methods: Changes in the average monthly mortality in the period from 2008 to 2019 were analysed (linear regression) in relation to the average temperatures and humidity in those months in the same time period in Zenica-Doboj Canton. Results: Overall mortality increased from 7.9 ‰ in 2008 to 10.2 ‰ in 2019. Overall and specific mortality rates for cardiovascular, malignant, respiratory and metabolic diseases followed seasonal change of ambient temperature and humidity. The monitoring trend showed strong determination degree for overall mortality and mortality for cardiovascular, malignant and respiratory diseases, while for metabolic diseases it was somewhat lower. The highest mortality rates were found in January (cold month), and in August (warm month); the lowest one was in May, September and October. There was a strong significant negative correlation between temperature and mortality rates, while the correlation between humidity and mortality rates was not significant. Conclusion: As we have proven that mortality rates followed seasonal changes in ambient temperature and determined months with the least mortality rate, the community must take measures to ensure microclimatic conditions for the survival of patients with cardiovascular, malignant, respiratory and metabolic diseases.
Keywords: air temperature; humidity; mortality rate